Dendritic cell subsets in the intestinal lamina propria: Ontogeny and function. (21st August 2013) - Persson, Emma K.; Scott, Charlotte L.; Mowat, Allan McI.; Agace, William W.
<x xml:space="preserve">Abstract</x> The intestinal mucosa is exposed to large amounts of foreign antigen (Ag) derived from commensal bacteria, dietary Ags, and intestinal pathogens. Dendritic cells (DCs) are believed to be involved in the induction of tolerance to harmless Ags and in mounting protective immune responses to pathogens and, as such, to play key roles in regulating intestinal immune homeostasis. The characterization of classical DCs (cDCs) in the intestinal lamina propria has been under intense investigation in recent years but the use of markers (including CD11c, CD11b, MHC class II), which are also expressed by intestinal MΦs, has led to some controversy regarding their definition. Here we review recent studies that help to distinguish cDCs subsets from monocyte‐derived cells in the intestinal mucosa. We address the phenotype and ontogeny of these cDC subsets and highlight recent findings indicating that these subsets play distinct roles in the regulation of mucosal immune responses in vivo.